Women Know Better What Other Women Think and Feel: Gender Effects on Mindreading across the Adult Life Span - Wacker, Renata; Bölte, Sven; Dziobek, Isabel (Frontiers in Psychology, 2017)
Research recurrently shows that females perform better than males on various mindreading tasks. The present study contributes to this growing body of literature by being the first to demonstrate a female own-gender mindreading bias using a naturalistic social cognition paradigm including female and male targets. We found that women performed better at reading others´ minds, and that they were specifically more capable to read female targets, an own-gender target effect absent in men. Furthermore, a non-linear negative effect of perceiver age on mindreading performance was examined within a sample covering the age range of 17-70 years, as indicated by a stronger performance decrease setting on by the age of 30 years and continuing throughout middle and old age. These findings add to a more comprehensive understanding of the contextual factors influencing mindreading performance in typically developing adults.